Philosophical Study of the Local Wisdom of “Guni Gelo” as Restorative Justice in Customary Law in Kangae District, Sikka Regency, NTT Province - Micael Josviranto; Yoseph Darius Purnama Rangga; Agustino Resen Wakhe (Journal of Law, Politic and Humanities, 2024)
The Issue of law is one that directly touches human life. One of the legal systems closely tied to humans since ancient times is customary law, which has developed orally. In Kangae District, Sikka Regency, there is a customary law term known as "Guni Gelo," which represents the local wisdom of the community. The aim of this study is to examine the philosophical values of the local wisdom "Guni Gelo" to ensure that it is properly implemented in accordance with the customary law that applies to the Sikka Regency community, specifically in Kangae District. The research methodology included several stages: initial observations, preparation of research instruments, instrument validation, data collection, verification of the validity of the collected data, and data analysis. The customary law of Guni Gelo is one of the local wisdom traditions in Kangae District, Sikka Regency, East Nusa Tenggara (NTT), which holds deep philosophical significance for its people. The philosophical value identified from the research results is the recognition of the inherent value of humanity itself.